Sacred Spaces on Screen: Redefining African Shrines in Nollywood’s Global Narrative - Emmanuel, Nzas (My University, 2024)
This research paper delves into the portrayal of African shrines in Nollywood, Africa’s largest movie industry, with a focus on rectifying the incomplete representation of these sacred spaces. The paper emphasizes the profound role that shrines play in shaping the lives of Africans, predating the advent of foreign religions in Nigeria, a nation deeply rooted in religious consciousness. Recommendations are presented, urging a critical review by the federal government and regulatory bodies overseeing the Nigerian movie industry to ensure a comprehensive and accurate portrayal of African cultural heritage. Additionally, the creative industry is encouraged to use forums judiciously to maintain a genuine African identity, especially concerning shrines. Academic departments in theater arts and cultural studies are urged to champion authentic representation, empowering future creators to preserve African identity amidst evolving global cinematic trends. The paper concludes by underscoring the significant responsibility of Nollywood in shaping perceptions of African culture and advocating for a more accurate depiction of African shrines on the global stage, aligning with broader goals of promoting cultural appreciation and sustainable development.
Keywords: African Identity; African Religion; African shrines; INTERDISCIPLINARY RESEARCH AREAS::Cultural heritage and cultural production; Nollywood; Rituals; Sacred Spaces